Forming Future Teachers’ Communicative Competences through the Student Scientific Society Activities - Roman S. Nagovitsyn (National Research Mordova State University, 2019)
Introduction. This article is devoted to the analysis of the process improving communicative qualities of graduates and future subject teachers through the integration of educational and extracurricular activities. The authors analyze main directions of implementation of interpersonal, group and organizational communication in teacher training. The purpose of the article is to substantiate the effectiveness of the program of developing communicative competences on the basis of project activities in the student scientific community by creating special diagnostic tools. Materials and Methods. As a methodological substantiation of the study, the competence approach is considered; the implementation of the latter, in conjunction with the systemic, innovation-technological, qualitative, activity-oriented and personality-oriented approaches, provides a higher qualitative level of vocational training of future teachers. At the theoretical stage of the study, the foreign and Russian pedagogical theory, practices, standards and solutions to the stated research problem were analyzed. To confirm the effectiveness of the experimental results, methods of mathematical statistical analysis were applied and a special diagnosis was created, compiled in accordance with the Professional Standard of the teacher based on content analysis of the contents of the answers, in terms of the availability of linguistic units of positive and negative connotations. The practical part of the research involved the student scientific community of the Pedagogical Institute. Results. Based on the created model for the content of the communicative competence of the future teacher, the author’s 72-hour program was developed for 6-month extra-curricular activities. It contained various forms of work: the implementation of brainstorming methods, communicative battles, a round table, essay writing, scientific stand-up, intellectual play, etc. The peculiarity of the program was that in each case, up to three roles were considered: coordinator, creative person, participant. The study presents a new perspective on the monitoring of the quality of education, in particular, the author’s diagnosis of analysis of communicative skills aimed at achieving goals of pedagogical activity . Discussion and Conclusion. Practical application of the provisions identified in the study on the integration of educational and extracurricular activities for the formation of communicative qualities of students can be realized in the organization of the educational and educational space of a higher educational institution of the pedagogical profile. The qualitative approach used in the study to analyze the labor intensity of educational disciplines in terms of counting credit units to estimate competencies can be applied as one of the indicators of monitoring basic educational programs. The study will be useful for teacher trainers wishing to improve the educational space of various learning or ganizations for this profile of training.